Routine Optical Clearing of 3D-Cell Cultures: Simplicity Forward - Nürnberg, Elina; Vitacolonna, Mario; Klicks, Julia; von Molitor, Elena; Cesetti, Tiziana; Keller, Florian; Bruch, Roman; Ertongur-Fauth, Torsten; Riedel, Katja; Scholz, Paul; Lau, Thorsten; Schneider, Richard; et al. (Frontiers in Molecular Biosciences, 2020)
Three-dimensional cell cultures, such as spheroids and organoids, serve as increasingly important models in fundamental and applied research and start to be used for drug screening purposes. Optical tissue clearing procedures are employed to enhance visualization of fluorescence-stained organs, tissues, and three-dimensional cell cultures. To get a more systematic overview about the effects and applicability of optical tissue clearing on three-dimensional cell cultures, we compared six different clearing / embedding protocols on seven types of spheroid- and chip-based three-dimensional cell cultures of approximately 300 µm in size that were stained with nuclear dyes, immunofluorescence, cell trackers, and cyan fluorescent protein. Subsequent whole mount confocal microscopy and semi-automated image analysis were performed to quantify the effects. Quantitative analysis included fluorescence signal intensity and signal-to-noise ratio as a function of z-depth as well as segmentation and counting of nuclei and immunopositive cells. In general, these analyses revealed five key points, which largely confirmed current knowledge and were quantified in this study. First, there was a massive variability of effects of different clearing protocols on sample transparency and shrinkage as well as on dye quenching. Second, all tested clearing protocols worked more efficiently on samples prepared with one cell type than on co-cultures. Third, z-compensation was imperative to minimize variations in signal-to-noise ratio. Fourth, a combination of sample-inherent cell density, sample shrinkage, uniformity of signal-to-noise ratio, and image resolution had a strong impact on data segmentation, cell counts, and relative numbers of immunofluorescence-positive cells. Finally, considering all mentioned aspects and including a wish for simplicity and speed of protocols – in particular, for screening purposes – clearing with 88 % Glycerol appeared to be the most promising option amongst the ones tested.